Effect of surface wetting resin on the color stability and microhardness of esthetic composites = Efecto de la resina humectante de superficies sobre la estabilidad del color y la microdureza de resinas compuestas estéticas - Cangul, Suzan; Erpacal, Begum; Adiguzel, Ozkan; Unal, Mehmet 1992-; Gunay, Ayse (2021)
Objective: The aim of this study was to evaluate and compare the effects of the superficial application of two different modeling resins on the surface microhardness and discoloration of composite resins. Material and Methods: The present study used two different composites and modeling resins. The composites were placed in plastic molds. Subsequently, the modeling resins were applied on the surface of the two composite groups. The microhardness and color pertaining to all the groups were evaluated. The current study used the One-Way ANOVA and Kruskal Wallis tests, in order to perform the statistical evaluation (p<0.05). Results: The present study compared the microhardness pertaining to the groups and the highest microhardness values were observed in the Estelite Asteria group (none), whereas the lowest values were observed in the GC Essentia group (Ultradent). Moreover, the current study evaluated the color stability and the greatest discoloration was observed in the control group of the GC Essentia group, whereas the least discoloration was observed in the Estelite Asteria group that included the samples prepared using Ultradent Wetting Resin. Conclusions: The results of the present study demonstrated that the use of modeling resins, which facilitate the placement of composite resins, reduced the microhardness and discoloration of composite resins. The aforementioned effect can be attributed to the variations in the structure of the filling. However, further studies are warranted to support and verify the results of the current study.
Objetivo: El objetivo del presente estudio fue evaluar y comparar los efectos de la aplicación superficial de dos resinas humectantes sobre la microdureza superficial y la decoloración de las resinas compuestas. Material y métodos: El presente estudio utilizó dos resinas humectantes y resinas de modelado diferentes. Las resinas compuestas se colocaron en moldes de plástico. Posteriormente, se aplicaron las resinas humectantes sobre la superficie de los dos grupos. Se evaluó la microdureza y el color de todos los grupos. El presente estudio utilizó las pruebas One-Way ANOVA y Kruskal Wallis, para realizar la evaluación estadística (p<0.05). Resultados: Los valores más altos de microdureza se observaron en el grupo Estelite Asteria, mientras que los menores valores se observaron en el grupo GC Essentia (Ultradent). La mayor decoloración se observó en el grupo control o el grupo GC Essentia, mientras que la menor decoloración se observó en el grupo Estelite Asteria con Ultradent Wetting Resin. Conclusiones: Los resultados del presente estudio demostraron que el uso de resinas humectantes, que facilitan la colocación de resinas compuestas, redujo la microdureza y decoloración de las resinas compuestas. El efecto mencionado anteriormente se puede atribuir a las variaciones en la estructura del relleno. Sin embargo, se necesitan más estudios para respaldar y verificar los resultados del presente estudio.
En revista Odóvtos, vol. 23, no.2 (abril 2021)
Descripción basada en el contenido visto el 08 de noviembre, 2024
También disponible en formato HTML y EPUB